SARAYLI BİR MUHALİFİN SİYASİ MÜCADELESİ: TEŞEBBÜS-İ ŞAHSİ VE ADEM-İ MERKEZİYET CEMİYETİ - (:unkn) unknown (My University, 2015)
0

Prince Sabahaddin opposed both Sultan Abdulhamit II and the "Union and Progress Society" with his political opinions. On 1906, he established the "Decentralization and Deconcentration Society" after the "Young Turk" Congress I in Paris. He began to publish the newspaper "Terakki" (the Progress) with the aim to contribute to the survival of the Ottoman Empire. In his arguments, he defined liberal individualism as the main component of decentralization. According to him, social reforms had to be supported by administrative reforms in accordance with social progress. It was, therefore, needed to strengthen the local democracy. However, for the "Union and Progress Society," "decentralization" was a dangerous concept that would lead to the disintegration of the Empire. They, therefore, did not accept Prince Sabahaddin's suggestions. During that period, there was a debate on the ways of strengthening the decentralization of the provincial administrations. Prince Sabahaddin maintained that the legal and political status of non-Muslim groups in the Empire was an example of "decentralization." However, he could not foresee the fact that the system of non-Muslim groups played a crucial role in the dissolution of the Ottoman Empire.
(Struggle of an Antagonist from the Palace)
Keywords: Hukuk